PEMBELAJARAN KONTEKSTUAL MELALUI KESENIAN DAN PEMENUHAN HAK ANAK PADA HOMESCHOOLING SEKOLAH MAHA - Untung, Untung; Burha, Zulkhair; Rahman, Harnita; B, Muhaemin (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research explains the learning process carried out at SekolahMaha homeschooling which uses contextual learning methods with art as a learning medium. SekolahMaha involves children in creating curriculum, study schedules, and learning subjects based on children's reflections and needs. This process is then packaged and presented through works of art. This research is qualitative research with an autoethnographic approach. Researchers are parents as well as facilitators and organizers of SekolahMaha. Data were analyzed using the concept of child protection based on the Convention on the Rights of the Child which is based on four main pillars, namely the principle of non-discrimination, the best interests of the child, prioritizing children's growth and development and listening to children's opinions. This research proves that SekolahMaha's homeschooling, which implements arts-based contextual learning, is based on fulfilling children's basic rights